Gambaran Motivasi Pemberian ASI dan Discharge Planning pada Ibu Postpartum di RSUD Raden Mattaher Jambi - Fiola Rosa Dwina; Indah Mawarti; Meinarisa Meinarisa; Sri Mulyani; Muthia Mutmainnah (Journal of Innovative and Creativity, 2026)
The study purpose was to describe breastfeeding motivation and discharge planning among postpartum mothers at RSUD Raden Mattaher Jambi, focusing on maternal adaptation to physical and psychological changes, readiness for breastfeeding, and preparedness for post-discharge care to support maternal and infant health. Materials and methods. This study employed a quantitative approach with a descriptive design and a cross-sectional method. The study was conducted in October 2025 in the inpatient wards and obstetric outpatient clinics, involving 65 postpartum mothers selected through total sampling. Data were collected using questionnaires on breastfeeding motivation and discharge planning, then analyzed univariately to describe the distribution of frequencies and percentage Results. Most postpartum mothers were aged 20–35 years (78.5%), had higher education (44.6%), were unemployed (66.2%), and were multiparous (84.6%). A total of 58.5% had high motivation, and 30.8% rated discharge planning as very good. Conclusions. The majority of postpartum mothers demonstrated good motivation for breastfeeding and perceived that discharge planning had been well implemented. Nevertheless, improvements are needed in the quality of education, family support, lactation facilities, and the consistency of discharge planning implementation and documentation.